Probing the Role of Surface Energetics of Electrons and their Accumulation in Photoreduction Processes on TiO2. Issue 25 (14th May 2014) - Molinari, Alessandra; Maldotti, Andrea; Amadelli, Rossano
Abstract We address the role of the energetics of photogenerated electrons in the reduction of 4‐nitrobenzaldehyde on TiO2. This model molecule bears two functional groups featuring different reducibilities. Electrochemistry shows that reduction to 4‐aminobenzyl alcohol occurs in entirely distinct potential ranges. Partial reduction of the NO2 group, affording 4‐aminobenzaldehyde, takes place through surface states at potentials positive of the flatband potential (Efb). Dark currents caused by reduction of the aldehyde group are observed only at potentials more negative than Efb, and the process requires an electron accumulation regime. Photocatalysis with TiO2 suspensions agrees with the electrochemical data. In particular, reduction of the nitro group is a relatively fast process (k=0.059 s−1), whereas that of the aldehyde group is slower (k=0.001 s−1) and requires electron photoaccumulation. Control of the photogenerated charge is a prospective means for achieving chemoselective reductions.